2020
DOI: 10.7819/rbgn.v22i0.4064
|View full text |Cite
|
Sign up to set email alerts
|

Rating changes and the impact on stock prices

Abstract: Purpose -The objective of this study is to analyze the impact of changes in credit ratings on the long-term return of Brazilian firms.Design/methodology/approach -We conducted an event study to measure how stock prices in the Brazilian stock exchange (B3) react to rating upgrades and downgrades by Moody's and S&P.Findings -Our sample presents positive and significant returns measured by the BHAR for ratings downgrades and non-significant ones for upgrades. Our data also show the important role of the previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Still, there was no significant difference in the average abnormal return before and after the announcement of the Investment Grade. The study by Baraccat et al [ 32 ] also showed no significant difference in stock returns when there was an increase in credit rating on the Brazilian stock exchange.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, there was no significant difference in the average abnormal return before and after the announcement of the Investment Grade. The study by Baraccat et al [ 32 ] also showed no significant difference in stock returns when there was an increase in credit rating on the Brazilian stock exchange.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…There was no significant difference in the average abnormal returns before and after the Investment Grade announcement. Another study that made an important contribution to the theory of market efficiency, conducted by Baraccat et al [ 32 ] aimed at analyzing the impact of changes in credit ratings on the long-term returns of Brazilian companies, by conducting an event study to measure how stock prices on the Brazilian Stock Exchange reacted with the appearance of upgrades and downgrades by Moody's and S&P. The results of the study show that stock returns are positive and significant when there is a downgrade and not significant when there is an increase in credit rating.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, the greatest informative effect was produced by rating downgrades. In fact, Pinto [28] found a statistically significant abnormal return only in the case of a rating downgrade. A study of the influence of credit ratings on the stock prices of companies on the Johannesburg Stock Exchange (RSA) in 2005-2015 [29] showed that, just as in mature economies, this market shows a significantly negative response only to rating downgrades.…”
Section: Literature Reviewmentioning
confidence: 96%
“…For certain companies, covering needs with medium-and long-term debt, regardless of the nature of the debt, will put the company in a position of insolvency in the eyes of bondholders, causing its value to fluctuate according to the level of debt chosen, or even according to its exposure to the risk of bankruptcy (Amira & Hafssa, 2021). Debt is also a multidimensional signal, it is the result of a need for financing in the face of expansion potential (Ding et al, 2020), but it can also be seen by others as an indication of financial difficulties (Amira & Hafssa, 2021;Baraccat et al, 2020;Gallagher et al, 2022). We use total debt/total equity: Debt/Eq < 2 and current ratio: CR > 1.…”
Section: Financial Performance Signals Used To Differentiate High Bm ...mentioning
confidence: 99%